Entwicklung und Erprobung eines Wäschersystems zur CO2‐Abreinigung aus Rauchgasen mithilfe alkalischer Reststoffe. Issue 3 (29th January 2013) - Bauer, Markus; Hopf, Norbert; Hofstetter, Eugen; Peiffer, Stefan
<x xml:space="preserve">Abstract</x> An innovative, technical approach for the reduction of CO2 emissions is presented that utilizes alkaline wastes to capture CO2 from flue gases in stable mineral form. Comprehensive pilot‐scale experiments were conducted with the developed flue gas scrubbing system at a power plant site. By optimizing the process parameters gas flux, CO2 partial pressure, circulation flux and suspension liquid‐to‐solid ratio, a CO2 binding of 40 – 90 g kg–1 waste could be reached and up to 25 % of the CO2 could be captured. The new technique is economically advantageous especially when both alkaline waste and CO2 are produced on site and when the carbonated products can be used as secondary resources.